High‐performance sulphur dioxide sensor: Unveiling the potential of photonic crystal fibre technology - A. H. M. Iftekharul Ferdous; Md. Mynuddin; Khalid Sifulla Noor (IET Nanodielectrics)
Abstract The authors present an innovative photonic crystal fibre (PCF) detector that has the ability to detect sulphur dioxide (SO2) gas. This deadly gas having no tone at all with a strong aroma. Our suggested sensor is designed with heptagonal cladding along with octagonal core. It displays exclusive performance in detecting SO2 with an elevated relative sensitivity (RS). The max RS for this sensor is 87.39% with a tiny Confinement Loss of 6.8194 × 10−4 dB/m and having a total loss of 1.80609 × 10−2 dB/m at optimum frequency of 1.8 THz. Suggested PCF sensor also has effective material loss of 0.017379 cm−1 and effective area of 5.39710 × 10−8 m2. Among the principal air pollutants that can irritate and make respiration tough is SO2 and prolonged exposure could be a factor in permanent breathing problems. It also contributes to the development of acid rain, which damages aquatic environments. Therefore, it becomes necessary to detect this harmful gas and that can be effectively done with the proposed PCF sensor. The suggested PCF sensor can be crucial to minimise the air pollution rate. It will play a vital role for the improvement of human health safety from this deadly element.